The Asia-Pacific Clinical Practice Guidelines for the Management of Frailty - Dent, Elsa; Lien, Christopher; Lim, Wee Shiong; Wong, Wei Chin; Wong, Chek Hooi; Ng, Tze Pin; Woo, Jean; Dong, Birong; de la Vega, Shelley; Hua Poi, Philip Jun; Kamaruzzaman, Shahrul Bahyah Binti; Won, Chang; et al. (Journal of the American Medical Directors Association, 2017)
To develop Clinical Practice Guidelines for the screening, assessment and management of the geriatric condition of frailty. An adapted Grading of Recommendations, Assessment, Development, and Evaluation approach was used to develop the guidelines. This process involved detailed evaluation of the current scientific evidence paired with expert panel interpretation. Three categories of Clinical Practice Guidelines recommendations were developed: strong, conditional, and no recommendation. Strong recommendations were (1) use a validated measurement tool to identify frailty; (2) prescribe physical activity with a resistance training component; and (3) address polypharmacy by reducing or deprescribing any inappropriate/superfluous medications. Conditional recommendations were (1) screen for, and address modifiable causes of fatigue; (2) for persons exhibiting unintentional weight loss, screen for reversible causes and consider food fortification and protein/caloric supplementation; and (3) prescribe vitamin D for individuals deficient in vitamin D. No recommendation was given regarding the provision of a patient support and education plan. The recommendations provided herein are intended for use by healthcare providers in their management of older adults with frailty in the Asia Pacific region. It is proposed that regional guideline support committees be formed to help provide regular updates to these evidence-based guidelines.